A Case Report of Moraxella catarrhalis Infection After Lumbar Spinal Fixation and Fusion - Xie Y; Jiang S; Liang Q; Hu X; He D; Wu X (Infection and Drug Resistance)
Yehong Xie, Shunning Jiang, Qiaoling Liang, Xuezhu Hu, Dahai He, Xiaoheng Wu Chengdu University of Traditional Chinese Medicine Third Clinical Medical College/Affiliated Third Hospital, Pidu District Traditional Chinese Medicine Hospital, Chengdu, Sichuan, 611730, People’s Republic of ChinaCorrespondence: Xiaoheng Wu, Pidu District Traditional Chinese Medicine Hospital, Chengdu, Sichuan, 611730, People’s Republic of China, Email xiaohengwu1997@126.comAbstract: Moraxella catarrhalis (MC) is an aerobic Gram-negative cocci known to cause respiratory tract infections in humans as an opportunistic pathogen, with infections in other body parts being rare. This case involves an elderly female patient with a medical history of hypertension, type 2 diabetes, coronary heart disease, and osteoporosis. Following coronary angiography and lumbar spine surgery prompted by lower back and left lower limb pain, the patient developed persistent pus discharge from the lumbar spine wound post-surgery, which did not respond to conventional anti-infection therapy, leading to her transfer to our hospital. Upon examination, Direct Radiography (DR) diagram revealed gas accumulation and bone curling in the 4– 5 intervertebral space, muscle layer, and fascia layer of the lumbar vertebrae. Subsequent culture of the wound pus confirmed the presence of MC, resulting in a diagnosis of postoperative lumbar spine infection. Treatment involved antibiotics administration, lesion clearance, spinal exploration, and autologous iliac bone transplantation for fusion, alongside the management of glucose levels and hypertension, anticoagulation therapy, as well as the use of Duhuo Jisheng Decoction to promote blood circulation and eliminate blood stasis. Following this comprehensive treatment approach, the patient achieved a full recovery and was discharged. To the best of our knowledge, this is the first reported case of Moraxella catarrhalis infection following lumbar spinal fixation and fusion in Sichuan Province, China. The exact cause of infection in this case remains unclear. However, this case emphasizes the importance of considering the colonization site and infection mechanism of MC beyond the respiratory tract, underscoring the need for vigilance in clinical practice beyond typical infection sites.Keywords: Moraxella catarrhalis, lumbar spinal, fixation and fusion, case report